Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
We have to solve this system of equations by elimination.
To do that, we substract (or add) one equation from the other in order to clear the value of one of the unknowns. In general, we have to multiply by a coefficient to cancel one of the unknowns.
In this case, if we add both equations, we get rid of "y" and can calculate the value of x:
[tex]\begin{gathered} 3x+2y=-8 \\ -x-2y=4 \\ \Rightarrow(3x+2y)+(-x-2y)=-8+4 \\ 3x-x+2y-2y=-4 \\ 2x+0y=-4 \\ x=-\frac{4}{2} \\ x=-2 \end{gathered}[/tex]With the value of x, we can solve for y:
[tex]\begin{gathered} -x-2y=4 \\ -(-2)-2y=4 \\ 2-2y=4 \\ 2-4=2y \\ -2=2y \\ y=-\frac{2}{2} \\ y=-1 \end{gathered}[/tex]Answer: The solution is x=-2 and y=-1.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.